STUDI KASUS: HAMBATAN GURU DALAM PENGEMBANGAN PERANGKAT AJAR BERBASIS KURIKULUM MERDEKA PADA MATA PELAJARAN IPAS KELAS IV DI SDN ALALAK SELATAN 1 - Amalia Fitri; Anita; Rahma Aulia Putri; Sri Kurnia Damayanti; Ahmad Suriansyah; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study focuses on identifying and analyzing various obstacles experienced by educators in designing learning instruments oriented towards the Merdeka Curriculum, particularly for IPAS subjects in grade IV at SDN Alalak Selatan 1. The research approach used is descriptive qualitative through the case study method. Information was collected using in-depth interviews, direct observation, and documentation review involving fourth-grade educators, the head of the education unit, and students as primary sources. The research findings reveal three fundamental obstacles, namely: (1) complexity in adapting to the Merdeka Curriculum structure, especially when describing learning achievement targets; (2) temporal constraints arising from the accumulation of professional responsibilities; and (3) complexity in designing differentiated learning activities. Various strategies have been implemented, including a cooperative approach in the procurement of online learning modules, the independent development of assessment instruments, and the optimization of digital smart boards. The recommendations proposed include the urgency of continuous training, the procurement of high-quality reference sources, and the formulation of a proportional time distribution policy to support the effective implementation of the Merdeka Curriculum.